2016
DOI: 10.1021/acs.jmedchem.6b00245
|View full text |Cite
|
Sign up to set email alerts
|

Searching for New Leads for Tuberculosis: Design, Synthesis, and Biological Evaluation of Novel 2-Quinolin-4-yloxyacetamides

Abstract: In this study, a new series of more than 60 quinoline derivatives has been synthesized and evaluated against Mycobacterium tuberculosis (H37Rv). Apart from the SAR exploration around the initial hits, the optimization process focused on the improvement of the physicochemical properties, cytotoxicity, and metabolic stability of the series. The best compounds obtained exhibited MIC values in the low micromolar range, excellent intracellular antimycobacterial activity, and an improved physicochemical profile with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 25 publications
2
50
0
Order By: Relevance
“…To date, these chemical starting points have led to the discovery of two new classes of QcrB inhibitors, the 2-quinolin-4-yloxyacetamides (QOA) and the arylvinylpiperazine amides. Several SAR studies of the QOAs have been reported and are in agreement regarding the potency of this chemical entity against M. tb, the lack of toxicity in a zebrafish model and the narrow-spectrum activity specific for M. tb [132,154,155]. Independent work through cross-resistance studies and isolation of resistance mutants harbouring the mutation T313A in QcrB confirmed cytochrome bcc as the target of QOAs [155,156].…”
Section: Inhibitors Of the Cyt-bcc-aa3 Complexsupporting
confidence: 54%
See 1 more Smart Citation
“…To date, these chemical starting points have led to the discovery of two new classes of QcrB inhibitors, the 2-quinolin-4-yloxyacetamides (QOA) and the arylvinylpiperazine amides. Several SAR studies of the QOAs have been reported and are in agreement regarding the potency of this chemical entity against M. tb, the lack of toxicity in a zebrafish model and the narrow-spectrum activity specific for M. tb [132,154,155]. Independent work through cross-resistance studies and isolation of resistance mutants harbouring the mutation T313A in QcrB confirmed cytochrome bcc as the target of QOAs [155,156].…”
Section: Inhibitors Of the Cyt-bcc-aa3 Complexsupporting
confidence: 54%
“…Independent work through cross-resistance studies and isolation of resistance mutants harbouring the mutation T313A in QcrB confirmed cytochrome bcc as the target of QOAs [155,156]. The solubility and stability of this series, as well as their in vivo potency, remain to be addressed [133,154]. The arylvinylpiperazine amides were generated through lead optimisation and SAR studies conducted with GW861072X from the GSK screen, which was an attractive starting point for its structural simplicity and potent activity against M. bovis and M. tb [76].…”
Section: Inhibitors Of the Cyt-bcc-aa3 Complexmentioning
confidence: 99%
“…Furthermore, they deduced that the amide bond was responsible for the observed metabolic lability. Further optimisation led to the development of a benzoxazole analogue ( 359 ), which possessed vastly improved metabolic stability and decreased hERG affinity, albeit with reduced M. tuberculosis inhibitory activity …”
Section: Tuberculosismentioning
confidence: 99%
“…During the preparation of this manuscript, two groups have reported the results of their studies of the QOA class, confirming compound potency, selectivity for M. tuberculosis and lack of toxicity in a Danio rerio (zebrafish) model. 14 Herein we report our efforts in optimizing the in vitro anti-tuberculosis activity of the more potent GSK QOA analogue 5 and also identify, via use of selective mutant strains, their cellular target as involving the cytochrome bc 1 complex.…”
Section: Introductionmentioning
confidence: 99%